Strategi Guru Pendidikan Agama Islam Dalam Mengembangkan Public Speaking Pada Peserta Didik - Dewi, Ratna; Juriana, Juriana; Sari, Kartika (LENTERNAL: Learning and Teaching Journal, 2023)
This research aims to develop the confidence of the students in performing public speaking well so that they can train them to speak in public both at school and outside of school. However, the problem in this study that took place at the MA An-Najah Payabenua is the need for a teacher's strategy of Islamic education in developing public speaking because there is still a lack of encouragement for a teacher's strategy to raise awareness and understanding among the pupils. This type of research uses qualitative research with a descriptive approach that describes a phenomenon as it is. Data collection is done through the methods of interviews, observations, and documentation. The results of this study show that the strategy of teachers of Islamic religious education developed public speaking at MA An-Najah Payabenua. This is the application of public speaking to the visual aspects, public speaking to the vocal aspects, and public speaking to the verbal aspects. Then supporting factors developed the ability of public speaking: students have mastered the Indonesian language well; students are already accustomed to group work; the results are presented in front of the classroom; and students frequently attend speeches, read poetry, tell stories, and attend religious lectures.